2009
DOI: 10.1002/adsc.200800702
|View full text |Cite
|
Sign up to set email alerts
|

Iron(III) Salt‐Catalyzed Nazarov Cyclization/Michael Addition of Pyrrole Derivatives

Abstract: The Nazarov cyclization of two types of pyrrole derivatives was effectively catalyzed by 5 mol% alumina-supported ironAwhich provided the desired cyclization with high trans selectivity in good to excellent yield. The cyclized product was next reacted with a vinyl ketone in the presence of the same iron salt to afford the corresponding Michael product. A sequential type Nazarov/Michael reaction of pyrrole derivatives has also been accomplished; the synthetic route to 4,5-dihydrocyclopenta[b]pyrrol-6A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 32 publications
(19 reference statements)
0
39
0
Order By: Relevance
“…14c Another interesting application is a Nazarov cyclization/Michael addition sequence, which has been used to obtain new polyfunctionalized cyclopentenones. 23 …”
Section: Introductionmentioning
confidence: 99%
“…14c Another interesting application is a Nazarov cyclization/Michael addition sequence, which has been used to obtain new polyfunctionalized cyclopentenones. 23 …”
Section: Introductionmentioning
confidence: 99%
“…We tested the reaction using various iron salts (FeCl 2 , FeBr 2 , Fe(acac) 2 , Fe(OAc) 2 , Fe(ClO 4 ) 2 ·6H 2 O, Fe(OTf) 2 , FeCl 3 , Fe(ClO 4 ) 3 ·nH 2 O, and Fe(acac) 3 ) and solvents (toluene, tetrahydrofuran (THF), 1,4‐dioxane, acetonitrile, dichloroethane, MeOH, H 2 O, and ionic liquids) using 90 as a model substrate. As anticipated, the desired Nazarov cyclization smoothly proceeded and the cyclized product 91 (R = H) was obtained in over 90% yield using 5 mol% of Fe(ClO 4 ) 3 ·Al 2 O 3 or Fe(BF 4 ) 2 ·6H 2 O as the catalyst (Figure ) 53. An X‐ray crystallographic analysis of the cyclized product 91 revealed the trans relationship between the α‐carbomethoxy group and the β‐phenyl group.…”
Section: Iron‐catalyzed Nazarov Cyclizationmentioning
confidence: 57%
“…The solvent choice was very important in the reaction and CH 2 Cl 2 or the ionic liquid, 1‐butyl‐3‐methylimidazolium bis(trifuluoromethyl)sulfonylamide ([bmim][NTf 2 ]), tributyl(2‐methoxyethyl)phosphonium bis(trifuluoromethyl)sulfonylamide ([P 444ME ][NTf 2 ]), or N,N ‐diethyl, N ‐(2‐methoxyethyl), N ‐methylammonium bis(trifuluoromethyl)sulfonylamide ([N 221ME ][NTf 2 ]) provided excellent results (Figure ) 53. The stereochemistry of the product 91 did not depend on the E/Z ratio of the starting compound 90 , and the Nazarov cyclization product 91 , which had a trans relationship between the α‐carbomethoxy group and the β‐phenyl group, was produced as the major isomer, while a trace amount of the cis isomer was produced in the CH 2 Cl 2 solvent system 53. It was revealed that only the trans ‐ 91 was obtained when the reaction was conducted in the IL solvent 53.…”
Section: Iron‐catalyzed Nazarov Cyclizationmentioning
confidence: 99%
“…thiophenes [8] or pyrroles [9], and the enantioselective Michael addition of thiols to α, β-unsaturated carbonyl compounds [10].…”
Section: Introductionmentioning
confidence: 99%